Scattering of electromagnetic waves by periodic structures - N. Stefanou; V. Karathanos; A. Modinos (Journal of Physics: Condensed Matter, 1992)
The authors consider periodic structures made of spheres embedded in a host material with a different dielectric function. They show how to calculate the reflection and transmission of electromagnetic waves by a slab of the material parallel to a given crystallographic plane. The method of calculation is based on a doubling-layer scheme which obtains the reflection and transmission matrix elements for the multilayer from those of a single layer. The reflection and transmission characteristics of the slab are related to the complex band structure of the photon field associated with the given crystallographic plane of the corresponding infinite crystal, which is introduced in the manner of the low-energy electron diffraction theory. They present numerical results which demonstrate the applicability of the method to real systems of current interest and point out some interesting physics which arose from their calculations. They show in particular that the nondegenerate bands of the photon field at the centre of the surface Brillouin zone do not couple to the incident radiation, leading to total reflection at normal incidence.